2018
DOI: 10.1037/xge0000453
|View full text |Cite
|
Sign up to set email alerts
|

Working memory updating and binding training: Bayesian evidence supporting the absence of transfer.

Abstract: As working memory (WM) predicts a wide range of other abilities, it has become a popular target for training interventions. However, its effectiveness to elicit generalized cognitive benefits is still under debate. Previous research yielded inconsistent findings and focused only little on the mechanisms underlying transfer effects. To disentangle training effects on WM capacity and efficiency, we evaluated near transfer to untrained, structurally different WM tasks and far transfer to closely related abilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 161 publications
(362 reference statements)
5
75
1
1
Order By: Relevance
“…The accuracy cut off was used to exclude blocks in which we assumed that participants were not attending to the task, and were guessing (i.e., responding randomly); guessing would be indicated by scores close to chance. It is common practice in cognitive control studies to apply an accuracy cut off for this reason (e.g., De Simoni & von Bastian, 2018;Kane, Poole, Tuholski & Engle, 2006;Rey-Mermet, Gade & Oberauer, 2018;Zwaan et al, 2017). The 60% accuracy cut off in the current study resulted in four participants in the group with DS and two participants in the TD group missing data from either the low or high memory load conditions.…”
Section: Accuracy Cut Offmentioning
confidence: 79%
“…The accuracy cut off was used to exclude blocks in which we assumed that participants were not attending to the task, and were guessing (i.e., responding randomly); guessing would be indicated by scores close to chance. It is common practice in cognitive control studies to apply an accuracy cut off for this reason (e.g., De Simoni & von Bastian, 2018;Kane, Poole, Tuholski & Engle, 2006;Rey-Mermet, Gade & Oberauer, 2018;Zwaan et al, 2017). The 60% accuracy cut off in the current study resulted in four participants in the group with DS and two participants in the TD group missing data from either the low or high memory load conditions.…”
Section: Accuracy Cut Offmentioning
confidence: 79%
“…Metaanalyses of transfer effects on cognitive control among children, young and older adults suggested a significant near-transfer effect and no convincing evidence of fartransfer [24,29,32]. The evidence from young adults indicates that working memory training did not elicit any improvements across all ranges of transfer [33], but produced short-term, specific training effects that do not generalize to measures of "real-world," such as intelligence, life ability, or academic performance [27,32]. These arguments suggested that there may be limitations in training only for certain components or tasks in cognitive control interventions.…”
Section: Behavioral Improvement and Transfer Effects Induced Bymentioning
confidence: 85%
“…BFs are therefore increasingly popular in both cognitive training research and tES studies (e.g. Biel & Friedrich, 2018;De Simoni & von Bastian, 2018;Morgan, were not stated in the pre-registered report) and were computed in JASP (The JASP Team., 2017) with default prior scales. Inverse BF (BF10) are reported to express the odds in favour of the alternative hypothesis (BDR training and/or stimulation has an effect) compared to the null (no effect of BDR training and/or tDCS).…”
Section: Analysis Planmentioning
confidence: 99%